Incidence Trends and Burden of Human Papillomavirus-Associated Cancers Among Women in the United States, 2001-2017. (24th August 2020) - Deshmukh, Ashish A; Suk, Ryan; Shiels, Meredith S; Damgacioglu, Haluk; Lin, Yueh-Yun; Stier, Elizabeth A; Nyitray, Alan G; Chiao, Elizabeth Y; Nemutlu, Gizem S; Chhatwal, Jagpreet; Schmeler, Kathleen; Sigel, Keith; et al.
Abstract: Human papillomavirus (HPV)-associated anal and oropharyngeal cancer incidence has increased in recent years among US women. However, trends in incidence and burden (annual number of cases) of noncervical HPV-associated cancers relative to cervical cancer remain unclear. Using the 2001-2017 US cancer statistics dataset, we evaluated contemporary incidence trends and burden (annual number of cases) of HPV-associated cancers among women by anatomic site, race or ethnicity, and age. Overall, cervical cancer incidence plateaued among White women but continued to decline among Black and Hispanic women. Anal cancer incidence surpassed cervical cancer incidence among White women aged 65-74 years of age (8.6 and 8.2 per 100 000 in 2015) and 75 years or older (6.2 and 6.0 per 100 000 in 2014). The noncervical cancer burden (n = 11 871) surpassed the cervical cancer burden (n = 11 527) in 2013. Development of efficacious screening strategies for noncervical cancers and continued improvement in cervical cancer prevention are needed to combat HPV-associated cancers among women.